2014
DOI: 10.1007/128_2013_505
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Transformations via C–C Bond Cleavage

Abstract: Catalytic asymmetric transformations operating by carbon-carbon (C-C) bonds cleavages have emerged as intriguing strategies to access transient organometallic species from different reaction pathways. The reactions and the applicable substrate range have expanded considerably over the last decade. This overview covers the main developments in this field. A major focus is placed on β-carbon eliminations of strained tert-alcohols and related processes which have been shown to be particularly versatile in a broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…While highly desirable, controlling both reactivity and stereochemistry constitutes a significant challenge during activation of inert chemical bonds. The recent advancement allows asymmetric C–H functionalization to emerge as a powerful tool for synthesis; by contrast, the corresponding asymmetric C–C cleavage/functionalization, though attractive for preparing chiral complex ring systems, has been much less developed . To date, the scope of transition metal-catalyzed asymmetric C–C activation has been primarily restricted to either the cleavage of an achiral C–C bond, e.g., an aryl–CN bond , or the C1–C8 bond in benzocyclobutenones, , or use of symmetrical substrates (Scheme a,b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While highly desirable, controlling both reactivity and stereochemistry constitutes a significant challenge during activation of inert chemical bonds. The recent advancement allows asymmetric C–H functionalization to emerge as a powerful tool for synthesis; by contrast, the corresponding asymmetric C–C cleavage/functionalization, though attractive for preparing chiral complex ring systems, has been much less developed . To date, the scope of transition metal-catalyzed asymmetric C–C activation has been primarily restricted to either the cleavage of an achiral C–C bond, e.g., an aryl–CN bond , or the C1–C8 bond in benzocyclobutenones, , or use of symmetrical substrates (Scheme a,b).…”
mentioning
confidence: 99%
“…The recent advancement allows asymmetric C−H functionalization to emerge as a powerful tool for synthesis; 1 by contrast, the corresponding asymmetric C−C cleavage/functionalization, though attractive for preparing chiral complex ring systems, has been much less developed. 2 To date, the scope of transition metal-catalyzed asymmetric C−C activation 3 has been primarily restricted to either the cleavage of an achiral C−C bond, e.g., an aryl−CN bond 2b,c or the C1−C8 bond in benzocyclobutenones, 2d,e or use of symmetrical substrates b). Despite the fact that chiral unsymmetrical C− C bonds are common, the corresponding catalytic asymmetric transformation involving activation of these bonds remains elusive (Scheme 1c).…”
mentioning
confidence: 99%
“…Sections and will be dedicated to acceptor- and donor-only activated cyclopropanes, respectively. These classes of substrates are more difficult to activate and have been less investigated, but recent exciting progress has been realized, especially based on transition-metal catalysis or formation of reactive intermediates, such as radicals or carbocations. Enantioselective methods have just started to emerge in this case.…”
Section: Introductionmentioning
confidence: 99%
“…40 It is our ambition to address this gap in catalytic atropisomer synthesis via carbon-carbon cleavage. 41,42 Miura and his co-workers did the pioneering work on this type of carbon-carbon bond cleavage and ring-opening cross-coupling reaction to give biaryl ketone derivatives. 43 It was found that decarbonylation reaction (releasing acetone) would take place when a,a-disubstituted arylmethanols were used.…”
Section: Introductionmentioning
confidence: 99%